The psychometric properties of the Gaming Addiction Scale in a sample of Portuguese college students - Dores, Artemisa R. (2022)
The recent inclusion of the gaming disorder in the ICD-11 brought a huge interest in this disorder. However, the assessment of behavioural disorders is still largely dependent on the instruments used. This study aims to describe the application of the Gaming Addiction Scale (GAS) to a sample of Portuguese college students and analyse its psychometric characteristics.